Left Atrium: A New Prognostic Marker and Therapeutic Target in Secondary Mitral Regurgitation? - Markos Koukos; Yannis Dimitroglou; Dimitrios Tsartsalis; Eirini Beneki; Elias Tolis; Dimitrios Patsourakos; Argyro Kalompatsou; Constantina Aggeli; Konstantinos Tsioufis (European Cardiology Review)
Mitral regurgitation (MR) is one of the most common valvular abnormalities worldwide and can be subdivided into primary and secondary causes. Atrial MR consists of a novel type of secondary MR (SMR), most often observed in patients with AF and heart failure with preserved ejection fraction. The main pathophysiological mechanism of atrial MR is mitral valve annular dilatation. Recently published studies have highlighted the clinical significance of left atrium (LA) evaluation in the early diagnosis and prognosis of patients with primary MR. However, there are little data regarding the role of the LA in SMR. The present literature review aims to elucidate the use of the echocardiographic parameters regarding LA evaluation in the prognosis prediction and therapeutic strategy of patients with SMR.